Thermally conductive sheet

By grinding carbon fiber X and surfaces in the thickness direction in the thermally conductive sheet, the problem of difficulty in reducing the thermal resistance value in electronic equipment is solved, and a thermally conductive sheet with a lower thermal resistance value is realized, which is suitable for high-heat electronic equipment.

CN116096792BActive Publication Date: 2025-02-25SEKISUI POLYMATECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180063025.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-30
Filing Date
2021-08-24
Publication Date
2025-02-25
Estimated Expiration
2041-08-24

Smart Images

  • Figure CN116096792B_ABST
    Figure CN116096792B_ABST
Patent Text Reader

Abstract

The present invention is a thermally conductive sheet comprising a matrix and carbon fibers X, wherein the matrix is ​​formed of an organic polymer, the carbon fibers X are oriented in the thickness direction of the sheet, and the proportion of carbon fibers (A) having a fiber length of 100 μm or less is 40% or more, and the proportion of carbon fibers (B) having a fiber length of 200 μm or more is 3 to 13% of the carbon fibers X. According to the present invention, a thermally conductive sheet having a low thermal resistance value can be provided, which can effectively reduce the thermal resistance value by polishing the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermally conductive sheet, and for example, to a thermally conductive sheet to be disposed between a heat generating body and a heat dissipating body for use. Background Art

[0002] In electronic devices such as computers, automobile parts, and mobile phones, a heat sink or other heat dissipation body is generally used to dissipate heat generated by heat generating bodies such as semiconductor components and mechanical parts. In order to improve the efficiency of heat transfer to the heat sink, it is known to arrange a thermally conductive sheet between the heat generating body and the heat sink.

[0003] Thermally conductive sheets are usually compressed when placed inside electronic devices, and require high flexibility. Therefore, they are formed by mixing a thermally conductive filler material with a high-flexibility polymer matrix such as rubber or gel. In addition, for thermally conductive sheets, it is widely known that anisotropic fillers such as carbon fibers are oriented in the thickness direction in order to improve the thermal conductivity in the thickness direction (for example, see Patent Documents 1 and 2).

[0004] In addition, in Patent Document 3, from the viewpoint of further improving thermal conductivity, an invention related to a thermally conductive sheet is recorded, in which an anisotropic filler such as carbon fiber is exposed on the surface of the sheet and the arithmetic mean curvature (Spc) of the peak vertices on the surface of the sheet is below a certain value. In the examples, it is shown that by performing surface grinding on a sheet made under certain conditions, the thermal resistance value can be reduced (i.e., the thermal conductivity can be improved).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-056315

[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-014534

[0009] Patent Document 3: International Publication No. 2020 / 067141 Summary of the invention

[0010] Problems to be solved by the invention

[0011] The invention described in Patent Document 3 provides a thermally conductive sheet with low thermal resistance and good heat dissipation. However, in recent years, as electronic devices have become more sophisticated, heat generation has increased, and a thermally conductive sheet with lower thermal resistance than before has been required.

[0012] Therefore, an object of the present invention is to provide a thermally conductive sheet having a lower thermal resistance value than conventional ones.

[0013] Means for solving problems

[0014] As a result of intensive studies, the inventors of the present application have found that a thermally conductive sheet comprising a matrix and carbon fibers X, wherein the matrix is ​​composed of an organic polymer, the carbon fibers X are oriented in the thickness direction of the sheet, and the carbon fibers X contain carbon fibers with long fiber lengths and carbon fibers with short fiber lengths at specific ratios, respectively, can effectively reduce the thermal resistance value by polishing the surface, thereby becoming a sheet with low thermal resistance value, and have completed the present invention.

[0015] That is, the present invention provides the following [1] to [6].

[0016] [1] A thermally conductive sheet comprising a matrix and carbon fibers X, wherein the matrix is ​​formed of an organic polymer, the carbon fibers X are oriented in the thickness direction of the sheet, and the carbon fibers X contain carbon fibers (A) having a fiber length of 100 μm or less in a proportion of 40% or more and carbon fibers (B) having a fiber length of 200 μm or more in a proportion of 3 to 13%.

[0017] [2] The thermally conductive sheet according to [1] above, wherein the proportion of carbon fibers (C) having a fiber length of 50 μm or less in the carbon fibers X is 5% or less.

[0018] [3] The thermally conductive sheet according to [1] or [2] above, further comprising flaky carbon powder.

[0019] [4] The thermally conductive sheet according to any one of [1] to [3] above, wherein a portion of the carbon fibers X is exposed on the surface of the sheet, and when observing the surface of a 1 mm×1 mm area, when the depth in the thickness direction from the highest point of the sheet to the deepest part of the sheet is set to 100%, an area S occupied by the sheet in a cross section perpendicular to the thickness direction at a position 40% along the thickness direction from the highest point of the sheet is 65% or more.

[0020] [5] The thermally conductive sheet according to any one of [1] to [4] above, wherein the thermal resistance value is 0.024°C·in 2 / W or less.

[0021] [6] The thermally conductive sheet according to any one of [1] to [5] above, wherein the thickness is 50 to 900 μm.

[0022] Effects of the Invention

[0023] According to the present invention, it is possible to provide a thermally conductive sheet having a low thermal resistance value, which can be effectively reduced by polishing the surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] [ Figure 1 ] is a schematic cross-sectional view showing one embodiment of the thermally conductive sheet of the present invention.

[0025] [ Figure 2 ] is a schematic cross-sectional view showing another embodiment of the thermally conductive sheet of the present invention.

[0026] [ Figure 3 ] is an explanatory diagram for the method of calculating the area S occupied by a piece.

[0027] [ Figure 4 ] is a schematic diagram of a thermal resistance measuring machine. DETAILED DESCRIPTION

[0028] [Thermal Conductive Sheet]

[0029] The thermally conductive sheet of the present invention comprises a matrix and carbon fibers X, wherein the matrix is ​​formed of an organic polymer, the carbon fibers X are oriented in the thickness direction of the sheet, and among the carbon fibers X, the proportion of carbon fibers (A) having a fiber length of 100 μm or less is 40% or more, and the proportion of carbon fibers (B) having a fiber length of 200 μm or more is 3 to 13%.

[0030] Hereinafter, the thermally conductive sheet of the present invention will be described in detail.

[0031] Figure 1 This is a thermally conductive sheet according to one embodiment of the present invention. It should be noted that the present invention is not limited to the contents of the drawings.

[0032] The thermally conductive sheet 10 according to the present embodiment includes a matrix 14 formed of an organic polymer and carbon fibers X. Specifically, the carbon fibers X are dispersed in the matrix 14 and are oriented in the thickness direction of the thermally conductive sheet 10. As the carbon fibers X are oriented, the thermal conductivity of the thermally conductive sheet 10 is improved.

[0033] Here, the state in which the carbon fibers X are oriented in the thickness direction of the thermally conductive sheet 10 refers to a state in which more than 60% of the carbon fibers X in terms of number have their major axis oriented within 20° to the thickness direction of the thermally conductive sheet 10. Such an oriented state can be confirmed by observing a cross section of the thermally conductive sheet 10 along the thickness direction using an electron microscope.

[0034] like Figure 1 As shown, the carbon fiber X is preferably partially exposed on the surface of the sheet. As a result, it is easy to increase the thermal conductivity in the thickness direction and improve the heat dissipation. In addition, although not shown, as described later, flaky carbon powder may also be contained together with the carbon fiber X.

[0035] In addition, the thermally conductive sheet 10 may contain a non-anisotropic filler 16. By containing the non-anisotropic filler 16 together with the carbon fibers X, a heat conduction path is easily formed, and the thermal conductivity in the thickness direction of the sheet is easily improved. It should be noted that the non-anisotropic filler 16 is not an essential component in the present invention. Figure 2 As shown in FIG. 1 , a thermally conductive sheet 20 may be provided that does not contain the non-anisotropic filler 16 . The thermally conductive sheet 20 is the same as the thermally conductive sheet 10 except that the non-anisotropic filler 16 is not provided.

[0036] Hereinafter, each component constituting the thermally conductive sheet of the present invention will be described in detail.

[0037] (Carbon Fiber X)

[0038] The carbon fiber X is composed of a plurality of carbon fibers having different fiber lengths. In the present invention, the carbon fibers X contain carbon fibers (A) having a fiber length of 100 μm or less at a ratio of 40% or more and carbon fibers (B) having a fiber length of 200 μm or more at a ratio of 3 to 13%.

[0039] If the proportion of carbon fibers (A) having a fiber length of 100 μm or less is less than 40%, the effect of reducing the thermal resistance value by grinding the surface of the thermal conductive sheet becomes low. In addition, in order to lower the thermal resistance value after grinding, it is preferred to lower the thermal resistance value before grinding. From this point of view, the proportion of carbon fibers (A) having a fiber length of 100 μm or less is preferably 43% or more, more preferably 45% or more, and further preferably 47% or more.

[0040] It should be noted that the ratio of the carbon fibers (A) having a fiber length of 100 μm or less refers to the ratio of the number of carbon fibers (A) having a fiber length of 100 μm or less in the entire carbon fibers X.

[0041] As described above, in the present invention, the proportion of carbon fibers (B) having a fiber length of 200 μm or more is 3 to 13%. If the proportion of carbon fibers (B) having a fiber length of 200 μm or more is less than 3%, the effect of reducing the thermal resistance value achieved by grinding the thermal conductive sheet becomes low. On the other hand, if the proportion of carbon fibers (B) having a fiber length of 200 μm or more is greater than 13%, the thermal resistance value before grinding becomes high, and therefore, as a result, the thermal resistance value after grinding also becomes high.

[0042] From the viewpoint of lowering the thermal resistance value of the thermally conductive sheet after polishing, the proportion of the carbon fibers (B) having a fiber length of 200 μm or more is preferably 3 to 11%, more preferably 3 to 8%, and even more preferably 3 to 5%.

[0043] The ratio of the carbon fibers (B) having a fiber length of 200 μm or more refers to the ratio of the number of the carbon fibers (B) having a fiber length of 200 μm or more in the entire carbon fibers X.

[0044] In the carbon fiber X, the proportion of carbon fibers (C) having a fiber length of 50 μm or less is preferably 5% or less. By setting the proportion of carbon fibers (C) having a fiber length of 50 μm or less to 5% or less, the effect of reducing the thermal resistance value by grinding is easily improved. The proportion of carbon fibers (C) is preferably 4% or less, and more preferably 3% or less.

[0045] It should be noted that the ratio of the carbon fibers (C) having a fiber length of 50 μm or less refers to the ratio of the number of the carbon fibers (C) having a fiber length of 50 μm or less in the entire carbon fibers X.

[0046] The average fiber length D50 of the carbon fiber X is preferably 50 to 150 μm, more preferably 70 to 130 μm, and further preferably 80 to 120 μm. If the average fiber length D50 of the carbon fiber X is above these lower limits, the carbon fibers are easily in contact with each other, and it is easy to ensure a heat transfer path. If the average fiber length D50 of the carbon fiber X is below these upper limits, it is easy to highly fill the carbon fiber in the matrix.

[0047] The ratio of carbon fiber (A), carbon fiber (B), and carbon fiber (C) in the carbon fiber X, and the average fiber length D50 can be obtained from a fiber length distribution curve obtained by taking carbon fiber X as a sample, with the horizontal axis being the fiber length and the vertical axis being the cumulative frequency. The fiber length distribution curve is a number-based fiber length distribution curve obtained by accumulating in order from carbon fibers with a small fiber length.

[0048] The fiber length distribution curve can be prepared by microscopic observation of the carbon fiber X. For example, the fiber length of more than 2000 carbon fibers constituting the carbon fiber X can be measured using an electron microscope and an optical microscope to prepare a fiber length distribution curve, and the proportion of carbon fiber (A), carbon fiber (B), and carbon fiber (C) can be calculated. In addition, the average fiber length D50 refers to the fiber length equivalent to 50% of the cumulative frequency. It should be noted that the fiber length distribution curve is prepared by excluding fibers with a fiber length of less than 30 μm. More specifically, the carbon fiber X used as a measurement sample can be prepared by separating it from the thermal conductive sheet. In addition, the carbon fiber X can be observed using an optical microscope, and after obtaining the observation image, the fiber length can be measured using the image analysis software "WinROOF" manufactured by Mitani Shoji Co., Ltd.

[0049] The carbon fiber X is a carbon fiber with a high aspect ratio, specifically, a carbon fiber with an aspect ratio exceeding 2, and preferably an aspect ratio of not less than 5. When the aspect ratio is greater than 2, the carbon fibers are easily oriented in the thickness direction, and the thermal conductivity of the thermally conductive sheet is easily improved.

[0050] In addition, the upper limit of the aspect ratio is not particularly limited, but is 100 in practical use.

[0051] It should be noted that the aspect ratio of carbon fiber refers to fiber length / fiber diameter.

[0052] The content of carbon fiber X in the thermal conductive sheet is preferably 30 to 500 parts by mass, more preferably 50 to 300 parts by mass, relative to 100 parts by mass of the matrix. When the content of carbon fiber X is greater than or equal to these lower limits, thermal conductivity is easily improved, and when the content of carbon fiber X is less than or equal to the upper limit, the viscosity of the mixed composition described later is easily appropriate, and the orientation of carbon fiber X is improved.

[0053] The carbon fiber X is preferably made of two or more carbon fibers having different average fiber lengths as raw materials, and more specifically, preferably uses a short fiber length carbon fiber component having an average fiber length of 50 to 120 μm and a long fiber length carbon fiber component having an average fiber length greater than 120 μm in combination.

[0054] The amount of the short-fiber carbon fiber component is preferably 20 to 490 parts by mass, more preferably 40 to 290 parts by mass, relative to 100 parts by mass of the matrix.

[0055] The long-fiber-length carbon fiber component is preferably contained in an amount of 3 to 100 parts by mass, more preferably 5 to 70 parts by mass, based on 100 parts by mass of the matrix.

[0056] From the viewpoint of improving the effect of reducing the thermal resistance value achieved by grinding the thermally conductive sheet and reducing the thermal resistance value after grinding, the mass ratio of the short fiber length carbon fiber component to the long fiber length carbon fiber component (short fiber length carbon fiber component / long fiber length carbon fiber component) is preferably 1.5 to 55, and more preferably 3 to 20.

[0057] The average fiber length of the short-fiber-length carbon fiber component is preferably 70 to 115 μm, more preferably 90 to 110 μm.

[0058] The average fiber length of the long-fiber-length carbon fiber component is preferably 130 to 300 μm, more preferably 140 to 260 μm.

[0059] The average fiber length of each of the short-fiber carbon fiber component and the long-fiber carbon fiber component mixed as raw materials can be determined by measuring the fiber lengths of 50 random carbon fibers using an electron microscope or an optical microscope and taking the average value thereof as the average fiber length.

[0060] Carbon fiber X is preferably graphitized carbon fiber. In graphitized carbon fiber, the crystal planes of graphite are connected along the fiber axis direction, and have high thermal conductivity in the fiber axis direction. Therefore, by making the fiber axis direction uniformly facing a predetermined direction, the thermal conductivity in a specific direction can be improved.

[0061] The carbon fiber X is not particularly limited, and the thermal conductivity along the anisotropic direction (i.e., the long axis direction) is usually 60 W / m·K or more, preferably 400 W / m·K or more. The upper limit of the thermal conductivity of the carbon fiber X is not particularly limited, and is, for example, 2000 W / m·K or less. The thermal conductivity can be measured by a laser flash method or a method in accordance with ASTM D5470.

[0062] The thermally conductive sheet preferably contains flaky carbon powder together with the carbon fibers X. By containing the flaky carbon powder, the effect of reducing the thermal resistance value by polishing the thermally conductive sheet can be further enhanced.

[0063] The content of the flaky carbon powder in the thermally conductive sheet is preferably 1 to 50 parts by mass, more preferably 5 to 40 parts by mass, and more preferably 10 to 30 parts by mass relative to 100 parts by mass of the matrix. If the content of the flaky carbon powder is at least these lower limits, the effect of reducing the thermal resistance value by grinding the thermally conductive sheet can be further improved, and if the content of the flaky carbon powder is at most these upper limits, the viscosity of the mixed composition described later is likely to become appropriate, and the orientation of the flaky carbon powder becomes good.

[0064] The aspect ratio of the flaky carbon powder exceeds 2, and the aspect ratio is preferably 5 or more. When the aspect ratio is greater than 2, the flaky carbon powder is easily oriented in the thickness direction, and the thermal conductivity of the thermally conductive sheet is easily improved. In addition, the upper limit of the aspect ratio is not particularly limited, but is practically 100. The aspect ratio of the flaky carbon powder refers to the length / thickness of the flaky carbon powder in the long axis direction.

[0065] As the flaky carbon powder, flaky graphite powder is preferred. In the flaky graphite powder, the crystal planes of graphite are connected along the in-plane direction of the flaky plane, and have high thermal conductivity in the in-plane direction. Therefore, by making the flaky planes uniformly face a predetermined direction, the thermal conductivity in a specific direction can be improved.

[0066] As the graphitized carbon materials such as the above-mentioned graphitized carbon fiber and flaky graphite powder, the material obtained by graphitizing the following raw materials can be used. For example, condensed polycyclic hydrocarbon compounds such as naphthalene, PAN (polyacrylonitrile), condensed heterocyclic compounds such as asphalt, etc., can be cited, and graphitized mesophase asphalt, polyimide, and polybenzoxazole with high graphitization degree are particularly preferably used. By using, for example, mesophase asphalt, so that in the spinning process described later, the asphalt is oriented along the fiber axis direction due to its anisotropy, it is possible to obtain a graphitized carbon fiber with excellent thermal conductivity along its fiber axis direction.

[0067] The graphitized carbon fiber can be a graphitized carbon fiber obtained by graphitizing the raw material after spinning, melting, and carbonization in sequence, and then pulverizing or cutting it to a specified particle size, or a graphitized carbon fiber obtained by graphitizing it after pulverizing or cutting it after carbonization. In the case of pulverizing or cutting before graphitization, the surface exposed again on the surface due to pulverization is prone to polycondensation reaction and cyclization reaction during graphitization, so that the degree of graphitization can be increased, thereby obtaining a graphitized carbon fiber with further improved thermal conductivity. On the other hand, in the case of pulverizing the spun carbon fiber after graphitization, the graphitized carbon fiber is rigid and therefore easy to pulverize, and a carbon fiber powder with a narrow fiber length distribution can be obtained by pulverizing it in a short time.

[0068] (Non-anisotropic filling material)

[0069] The thermally conductive sheet of the present invention preferably contains a non-anisotropic filler. The non-anisotropic filler is a thermally conductive filler contained in the thermally conductive sheet separately from the carbon fibers X, and is a material that imparts thermal conductivity to the thermally conductive sheet together with the carbon fibers X. By filling the non-anisotropic filler, the viscosity increase can be suppressed in the pre-curing stage of the sheet, and the dispersibility becomes good. In addition, between the carbon fibers X, for example, if the fiber length becomes large, it is not easy to increase the contact area between the fillers, but by filling the non-anisotropic filler therebetween, a heat transfer channel can be formed, and a thermally conductive sheet with high thermal conductivity can be obtained.

[0070] The non-anisotropic filler is a filler that does not substantially have anisotropy in shape, and is a filler that does not orient in a predetermined direction even under an environment where the carbon fibers X are oriented in a predetermined direction, such as when magnetic lines of force are generated or shear forces are applied as described later.

[0071] For the non-anisotropic filler, its aspect ratio is 2 or less, preferably 1.5 or less. By containing a non-anisotropic filler with a low aspect ratio, a filler with thermal conductivity is appropriately sandwiched in the gaps between the carbon fibers X, and a thermally conductive sheet with high thermal conductivity can be obtained. In addition, by making the aspect ratio less than 2, the viscosity of the mixed composition described later is prevented from increasing, and high filling can be achieved.

[0072] Specific examples of the anisotropic filler include metals, metal oxides, metal nitrides, metal hydroxides, carbon materials, oxides other than metals, nitrides, carbides, etc. Examples of the shape of the anisotropic filler include spherical shapes and irregular powders.

[0073] Among the non-anisotropic fillers, examples of metals include aluminum, copper, nickel, etc., examples of metal oxides include aluminum oxide (aluminum oxide), magnesium oxide, zinc oxide, etc., and examples of metal nitrides include aluminum nitride, etc. Examples of metal hydroxides include aluminum hydroxide. In addition, examples of carbon materials include spherical graphite, etc. Examples of oxides, nitrides, and carbides other than metals include quartz, boron nitride, silicon carbide, etc.

[0074] Among the above, the non-anisotropic filler is preferably selected from alumina, aluminum, zinc oxide, boron nitride, and aluminum nitride. In particular, from the viewpoint of filling properties and thermal conductivity, aluminum and alumina are preferred, and alumina is more preferred.

[0075] As the anisotropic filler, the above-mentioned materials may be used alone or in combination of two or more.

[0076] The average particle size of the non-anisotropic filler is preferably 0.1 to 50 μm, more preferably 0.5 to 35 μm. In addition, it is particularly preferably 1 to 15 μm. By making the average particle size 50 μm or less, it is not easy to cause adverse conditions such as disturbing the orientation of the carbon fiber X. In addition, by making the average particle size 0.1 μm or more, the specific surface area of ​​the non-anisotropic filler will not become larger than necessary, and even if a large amount is mixed, the viscosity of the mixed composition is not easy to increase, and it is easy to highly fill the non-anisotropic filler.

[0077] For example, at least two types of anisotropic fillers having different average particle sizes may be used as the anisotropic filler.

[0078] It should be noted that the average particle size of the non-anisotropic filler can be measured by observation using an electron microscope or the like. More specifically, the particle sizes of 50 random non-anisotropic fillers can be measured using, for example, an electron microscope or an optical microscope, and the average value (arithmetic mean) thereof can be taken as the average particle size. Alternatively, the average particle size is the volume average particle size of the particle size distribution measured using a laser diffraction scattering method (JIS R1629).

[0079] The content of the anisotropic filler is preferably in the range of 100 to 800 parts by mass, more preferably in the range of 150 to 700 parts by mass, based on 100 parts by mass of the matrix.

[0080] For the non-anisotropic filler, by setting it to 100 parts by mass or more, the amount of the non-anisotropic filler sandwiched between the gaps between the carbon fibers X becomes sufficient, and the thermal conductivity becomes good. On the other hand, by setting it to 800 parts by mass or less, the effect of improving the thermal conductivity corresponding to the content can be obtained, and the non-anisotropic filler does not hinder the thermal conduction by the carbon fibers X. In addition, by setting it within the range of 150 to 700 parts by mass, the thermal conductivity of the thermally conductive sheet is excellent, and the viscosity of the mixed composition becomes appropriate.

[0081] (Matrix)

[0082] The thermally conductive sheet contains a matrix formed of an organic polymer. The matrix is ​​an organic polymer such as an elastomer or rubber, and preferably a matrix formed by curing a liquid polymer composition (curable polymer composition) composed of a mixed system such as a main agent and a curing agent. The curable polymer composition may be, for example, a composition composed of an uncrosslinked rubber and a crosslinking agent, or a composition containing a monomer, a prepolymer, and a curing agent. In addition, the curing reaction may be room temperature curing or thermal curing.

[0083] The matrix formed by the curable polymer composition can be exemplified by silicone rubber. In the case of silicone rubber, as the matrix (curable polymer composition), it is preferred to use an addition reaction curable silicone. In addition, more specifically, as the curable polymer composition, a composition containing an alkenyl-containing organopolysiloxane and a hydrogen organopolysiloxane can be used.

[0084] As rubber, in addition to the above, various synthetic rubbers can also be used, and specific examples include acrylic rubber, nitrile rubber, isoprene rubber, polyurethane rubber, ethylene propylene rubber, styrene-butadiene rubber, butadiene rubber, fluororubber, butyl rubber, etc. When these rubbers are used, the synthetic rubber may be cross-linked in the thermally conductive sheet or may remain in an uncross-linked (i.e., uncured) state. Uncross-linked rubber is mainly used in the case of flow orientation.

[0085] When crosslinking (ie, curing) is performed, as described above, the matrix may be a matrix obtained by curing a curable polymer composition containing an uncrosslinked rubber composed of these synthetic rubbers and a crosslinking agent.

[0086] In addition, as the elastomer, thermoplastic elastomers such as polyester thermoplastic elastomers and polyurethane thermoplastic elastomers, and thermosetting elastomers formed by curing a liquid polymer composition of a mixed system consisting of a main agent and a curing agent can also be used. For example, a polyurethane elastomer formed by curing a polymer composition containing a polymer having a hydroxyl group and an isocyanate can be exemplified.

[0087] Among the above, silicone rubber, particularly addition reaction curing silicone, is preferably used because, for example, the matrix after curing is particularly soft and the filling properties of carbon fiber, flaky carbon powder mixed as needed, and anisotropic filler are good.

[0088] In addition, the polymer composition used to form the matrix may be composed of a polymer compound monomer or a polymer compound and a plasticizer. The plasticizer is suitable for use in the case of using synthetic rubber, and the inclusion of the plasticizer can improve the flexibility of the polymer matrix when not cross-linked.

[0089] When the content of the matrix is ​​expressed as a filling rate based on volume (volume filling rate), it is preferably 20 to 50% by volume, more preferably 25 to 45% by volume, relative to the total amount of the thermally conductive sheet.

[0090] (additive)

[0091] In the thermally conductive sheet, various additives may be further mixed into the matrix within a range that does not impair the function of the thermally conductive sheet. Examples of additives include at least one additive selected from dispersants, coupling agents, adhesives, flame retardants, antioxidants, colorants, anti-settling agents, and the like. In addition, when the curable polymer composition is crosslinked or cured as described above, a crosslinking accelerator or a curing accelerator that promotes crosslinking or curing may be mixed as an additive.

[0092] [Method for producing thermally conductive sheet]

[0093] The thermally conductive sheet of the present invention is not particularly limited, but is preferably produced, for example, by a method comprising the following steps (A) and (B).

[0094] Step (A): a step of obtaining an oriented molded body in which carbon fibers X are oriented in one direction, which is the thickness direction, in a thermally conductive sheet

[0095] Step (B): a step of cutting the oriented molded body into a sheet to obtain a thermally conductive sheet

[0096] Hereinafter, each step will be described in more detail.

[0097] <Step (A)>

[0098] In step (A), for example, an oriented molded body is formed from a mixed composition containing a polymer composition as a raw material of a matrix, carbon fiber X, and flaky carbon powder and a non-anisotropic filler mixed as needed. The mixed composition is preferably cured to form an oriented molded body. More specifically, the oriented molded body can be obtained by a magnetic field orientation method or a flow orientation method, among which the magnetic field orientation method is preferred.

[0099] (Magnetic field orientation method)

[0100] In the magnetic field orientation method, a mixed composition containing a liquid polymer composition that becomes a matrix after solidification, carbon fibers X, and flaky carbon powder and a non-anisotropic filler mixed as needed is injected into a casting container, etc., and then placed in a magnetic field to orient the carbon fibers X and the flaky carbon powder mixed as needed along the magnetic field, and then the polymer composition is solidified to obtain an oriented molded body. As the oriented molded body, it is preferable to prepare a block-shaped oriented molded body.

[0101] In addition, a release film may be disposed in the mold at the portion in contact with the mixed composition. The release film may be, for example, a resin film with good release properties or a resin film with one side subjected to a release treatment using a release agent. By using a release film, the oriented molded body can be easily released from the mold.

[0102] In order to carry out magnetic field orientation, the viscosity of the mixed composition used in the magnetic field orientation method is preferably 10 to 300 Pa·s. By setting it to 10Pa·s or more, each filler is not easy to settle. In addition, by setting it to 300Pa·s or less, the fluidity becomes good, and the magnetic field can be used to properly orient the carbon fiber X and the flaky carbon powder mixed as needed, and the undesirable situation that the orientation is too time-consuming will not occur. It should be noted that the so-called viscosity is the viscosity measured at a rotation speed of 10 rpm at 25°C using a rotational viscometer (Brookfield viscometer DV-E, spindle SC4-14).

[0103] However, when using carbon fibers X that are not easy to settle, flaky carbon powder, or anisotropic filler, or when using additives such as an anti-settling agent, the viscosity of the mixed composition may be less than 10 Pa·s.

[0104] In the magnetic field orientation method, as a magnetic field line generating source for applying magnetic field lines, superconducting magnets, permanent magnets, electromagnets, etc. can be cited, but from the aspect of being able to generate a magnetic field with a high magnetic flux density, superconducting magnets are preferred. The magnetic flux density of the magnetic field generated by these magnetic field line generating sources is preferably 1 to 30 Tesla. If the magnetic flux density is made greater than 1 Tesla, it becomes easy to orient the carbon fiber. In addition, by making the magnetic flux density less than 30 Tesla, it becomes possible to manufacture practically.

[0105] The polymer composition can be cured by heating, for example, at a temperature of about 50 to 150° C. The heating time is, for example, about 10 minutes to 3 hours.

[0106] (Flow Orientation Method)

[0107] In the flow orientation method, a shear force is applied to the mixed composition to produce a preliminary sheet in which the carbon fibers X and the flaky carbon powder mixed as required are oriented in the plane direction, and a plurality of these sheets are stacked to produce a stacked block, which is used as an oriented molded body.

[0108] More specifically, in the flow orientation method, first, carbon fiber X and flaky carbon powder, non-anisotropic filler, and various additives are mixed into the polymer composition and stirred to uniformly disperse the mixed solids to prepare the mixed composition. Here, the polymer compound used in the polymer composition may include a polymer compound that is liquid at room temperature (23° C.) or a polymer compound that is solid at room temperature. In addition, the polymer composition may contain a plasticizer.

[0109] The mixed composition has a relatively high viscosity in order to apply shear force when the mixed composition is stretched into a sheet form, and the viscosity of the mixed composition is preferably 3 to 500 Pa·s. In order to obtain the above viscosity, the mixed composition is preferably mixed with a solvent.

[0110] Next, the mixed composition is stretched flatly while applying shear force to the mixed composition, and formed into a sheet (preparatory sheet). By applying shear force, the carbon fiber X and the flaky carbon powder mixed as needed can be oriented in the shear direction. As a means of forming a sheet, for example, the mixed composition can be applied on the substrate film by a coating applicator such as a rod coater, a scraper, or extrusion molding, ejection from a nozzle, etc., and then dried as needed, or the mixed composition is semi-cured. The thickness of the preparatory sheet is preferably set to about 50 to 5000 μm. In the preparatory sheet, the carbon fiber X and the flaky carbon powder mixed as needed are oriented in one direction along the surface direction of the sheet.

[0111] Next, multiple preparatory sheets are repeatedly stacked in the same orientation direction, and then the mixed composition is cured as needed by heating, ultraviolet irradiation, etc., and the preparatory sheets are bonded to each other by heating and pressing, thereby forming a stacked block, which can be used as an oriented molded body.

[0112] <Process (B)>

[0113] In step (B), the oriented molded body obtained in step (A) is cut by slicing or the like perpendicularly to the direction in which the carbon fibers X are oriented, thereby obtaining a thermally conductive sheet. Slicing can be performed, for example, by a shear knife, a laser, or the like. The thermally conductive sheet is cut by slicing or the like, so that a portion of the carbon fibers X is exposed from the matrix on each surface as the cut surface. The exposed carbon fibers X are oriented in the thickness direction without being tilted.

[0114] Here, the E-type hardness of the oriented molded body as defined in JIS K6253 is preferably 10 to 80, more preferably 20 to 70. When the E-type hardness is 10 to 80, when the sheet-like molded body is sliced, the matrix is ​​cut more actively than the carbon fibers X, and the carbon fibers X can be easily exposed.

[0115] As described above, the thermally conductive sheet of the present invention obtained through the above steps (A) and (B) can be effectively reduced in thermal resistance by surface polishing, thereby becoming a thermally conductive sheet with low thermal resistance. Therefore, it is preferred that a step (C) of polishing the surface of the thermally conductive sheet is provided after steps (A) and (B).

[0116] <Process (C)>

[0117] Step (C) is a step of polishing the surface of the thermally conductive sheet.

[0118] In step (C), the surface of the thermally conductive sheet obtained in step (B) where the carbon fibers X are exposed is polished. The surface polishing can be performed using, for example, polishing paper, polishing film, polishing cloth, polishing tape, or the like.

[0119] As properties of the grinding paper, the average particle size (D50) of the abrasive grains contained therein is preferably 0.1 to 100 μm, more preferably 9 to 60 μm. In addition, the particle size of the abrasive grains of the grinding paper is preferably #120 to 20000, preferably #300 to 15000, and more preferably #320 to 4000.

[0120] Regarding the polishing method, in addition to continuously contacting the surface of the thermally conductive sheet with polishing paper in the same linear direction, the following methods can be used: polishing by reciprocating a certain distance, polishing by rotating in the same direction, or polishing by contacting in various directions.

[0121] In addition, the degree of polishing can be performed while observing the surface state, for example, in the case of reciprocating polishing, it is preferably 1 to 300 reciprocating times, more preferably 2 to 200 times, and even more preferably 3 to 50 times. Specifically, it is preferred to polish until the protruding length of the carbon fiber X becomes 100 μm or less. It is further preferred to polish until the protruding length becomes 50 μm or less.

[0122] [Surface state of thermally conductive sheet]

[0123] In the thermally conductive sheet of the present invention, as described above, it is preferred that a part of the carbon fibers X be exposed on the surface of the sheet. In addition, from the viewpoint of reducing the thermal resistance value, it is also preferred that the surface state of the thermally conductive sheet be as follows.

[0124] The preferred surface state of the thermally conductive sheet is schematically shown in FIG. Figure 3 When observing the thermally conductive sheet in a 1mm×1mm area from the surface, when the depth h in the thickness direction from the highest point P of the sheet to the deepest part Q of the sheet is set to 100%, in the cross section R perpendicular to the thickness direction at a position 40% along the thickness direction of the sheet from the highest point P (i.e., a position 0.4h along the thickness direction of the sheet from the highest point P), the area S occupied by the sheet is preferably 65% ​​or more.

[0125] If the area S occupied by the sheet is 65% or more, the thermal resistance of the thermally conductive sheet can be further reduced. The reason is not clear, but it is believed that such a specific surface state of the thermally conductive sheet means that the surface of the sheet is relatively smooth, which makes it easy to contact with the heat source, etc., resulting in a lower thermal resistance.

[0126] From the viewpoint of further reducing the thermal resistance value, the area S occupied by the sheet is preferably 66% or more, more preferably 68% or more. The upper limit of the area occupied by the sheet is not particularly limited, and the area S occupied by the sheet is usually 95% or less.

[0127] The highest point P of the sheet is the highest position of the sheet in the observation area, and is usually the tip of the carbon fiber X exposed from the surface. The deepest part Q of the sheet is the innermost part of the sheet in the concave part on the surface 10A of the sheet in the observation area.

[0128] In addition, the area S occupied by the sheet in the section R perpendicular to the thickness direction at the 40% position (0.4h position) along the thickness direction of the sheet starting from the highest point P refers to the proportion of the area of ​​the components constituting the sheet (matrix, carbon fiber X, etc.) in the section R (area 1mm×1mm).

[0129] It should be noted that the area S occupied by the flakes can be obtained by observing a 1 mm×1 mm region at 10 locations, finding the area occupied by the flakes at each location, and finding the average value of the areas.

[0130] The thermally conductive sheet having an area S of a certain size or more can be obtained, for example, through the above-mentioned steps (A) to (C), but the production method is not particularly limited.

[0131] The thermal resistance of the thermally conductive sheet is preferably 0.024°C·in 2 / W or less, more preferably 0.022℃·in 2 / W or less. If the thermal resistance value is this value, it will be a thermally conductive sheet that easily transfers heat from the heating element to the heat sink. The smaller the thermal resistance value, the better, usually 0.001℃·in 2 / W or more. It should be noted that the thermal resistance value is a thermal resistance value in the thickness direction of the thermally conductive sheet.

[0132] The thermally conductive sheet having such a thermal resistance value is not particularly limited, and can be obtained, for example, by producing a thermally conductive sheet having a sheet area S of a certain value or more.

[0133] <Surface parameters (Spc, Sa, Sdr)>

[0134] The arithmetic mean curvature (Spc) of the peak apex of the thermally conductive sheet of the present invention is preferably 18000 (1 / mm) or less. If the arithmetic mean curvature (Spc) of the peak apex is 18000 (1 / mm) or less, the contact area with the heat generating element or the like becomes larger, and the thermal resistance value can be reduced.

[0135] The arithmetic mean curvature (Spc) of the peak apex is preferably 17000 (1 / mm) or less, more preferably 16000 (1 / mm) or less. In addition, the arithmetic mean curvature (Spc) of the peak apex is preferably 1000 (1 / mm) or more, more preferably 5000 (1 / mm) or more.

[0136] The arithmetic mean curvature (Spc) of the peak vertex is a parameter that represents the arithmetic mean of the principal curvatures of the peak vertex in the defined area, measured in accordance with ISO 25178. A small value indicates that the point of contact with the heating element, etc. is curved. On the other hand, a large value indicates that the point of contact with the heating element, etc. is sharp.

[0137] It should be noted that the position of the curved contact point is not fixed, but for example, the end or end face of the carbon fiber exposed on the surface, or the surface composed of the end of the carbon fiber and the surface of the matrix may become the curved contact point.

[0138] The arithmetic mean curvature (Spc) of the peak apex can be measured by using a commercially available laser microscope to measure a predetermined measurement area (e.g., 1 mm2 It is calculated based on the surface contour of the two-dimensional area.

[0139] In order to make the arithmetic mean curvature (Spc) of the peak apex less than 18000 (1 / mm), for example, abrasive paper with a particle size of #120 to 20000 can be used, and the number of grindings corresponding to the particle size can be appropriately set to perform surface grinding treatment. In addition, if necessary, the E hardness of the above-mentioned oriented molded body can be set to about 10 to 80, and it can be sliced ​​into sheets and subjected to the above-mentioned grinding treatment.

[0140] The arithmetic mean height (Sa) of the surface of the thermally conductive sheet is preferably 20 μm or less, more preferably 1 to 15 μm. By making the arithmetic mean height (Sa) 20 μm or less, the surface of the sheet has smoothness, the contact area with the heating element is increased, and the thermal resistance value can be reduced. The arithmetic mean height (Sa) can be measured using a commercially available surface property measuring machine, specifically, it can be measured using the method described in the examples.

[0141] In order to make the arithmetic mean height (Sa) less than 20 μm, for example, a coarser grinding paper among grinding papers with a grit of #120 to 20000 may be used, and the number of grindings may be appropriately set according to the grit to perform surface grinding.

[0142] In addition, the surface of the thermally conductive sheet preferably has an interface development area ratio (Sdr) of 70 or less, and more preferably 1 to 60. Even when the carbon fibers are exposed from the surface of the thermally conductive sheet and the surface of the sheet is convex and concave, by setting the interface development area ratio (Sdr) to 70 or less, the surface of the sheet has smoothness, and the contact area with the heat generating element or the like becomes larger, thereby reducing the thermal resistance value.

[0143] It should be noted that the developed area ratio (Sdr) of the interface is the ratio of the developed area (surface area) of the defined region to the area of ​​the defined region (e.g. 1 mm 2 ) increases, and the developed area ratio Sdr of a completely flat surface becomes 0. The developed area ratio (Sdr) of the interface can be measured by the method described in the Examples.

[0144] In order to make the developed area ratio (Sdr) of the interface less than 70, for example, coarser grinding paper among grinding papers with a grit of #120 to 20000 can be used, and the number of grindings corresponding to the grit can be appropriately set to perform surface grinding.

[0145] [thickness]

[0146] The thickness of the thermally conductive sheet of the present invention can be appropriately selected according to the shape and application of the electronic device on which the sheet is mounted, but is preferably 50 to 900 μm, more preferably 50 to 800 μm, and even more preferably 150 to 400 μm. Even when the thermally conductive sheet of the present invention is relatively thin, the thermal resistance value can be kept below a certain level.

[0147] [use]

[0148] The thermally conductive sheet can be used inside electronic devices, etc. Specifically, the thermally conductive sheet is sandwiched between the heating element and the radiator, and the heat generated by the heating element is transferred to the radiator, and the heat is dissipated from the radiator. Here, as the heating element, various electronic components such as CPU, power amplifier, battery and other power sources used inside the electronic device can be cited. In addition, the radiator can be a radiator, a heat pipe, a heat pump, a metal housing of an electronic device, etc. The thermally conductive sheet is used in a manner that the two surfaces are respectively in close contact with the heating element and the radiator and compressed.

[0149] Example

[0150] Hereinafter, the present invention will be described in more detail using examples, but the present invention is not limited to these examples.

[0151] In the present example, the physical properties of the thermally conductive sheet were evaluated by the following methods.

[0152] [Proportion of carbon fibers classified by fiber length, average fiber length D50]

[0153] For the carbon fibers X contained in the thermally conductive sheet, the ratio of carbon fibers (A) having a fiber length of 100 μm or less, the ratio of carbon fibers (B) having a fiber length of 200 μm or more, and the ratio of carbon fibers (C) having a fiber length of 50 μm or less were calculated as follows.

[0154] Carbon fiber X was separated from the ground thermally conductive sheet using an organosilicon solvent (KSR-1 manufactured by Kanto Chemical Co., Ltd.). Then, for the separated product, an observation image (image) was obtained using an optical microscope (digital microscope VHX-900 manufactured by Keyence Co., Ltd.), and the fiber length of each of about 2,000 carbon fibers was measured using image analysis software WinROOF2015 (manufactured by Mitani Shoji Co., Ltd.). Next, a fiber length distribution curve was obtained with the horizontal axis being the fiber length and the vertical axis being the cumulative frequency (quantity basis). Then, using the fiber length distribution curve, the proportions of carbon fiber (A), carbon fiber (B), and carbon fiber (C) in carbon fiber X were respectively obtained. It should be noted that at this time, the fiber length distribution curve is made by excluding fibers with a fiber length of less than 30 μm.

[0155] Furthermore, the average fiber length D50 of the carbon fibers X is determined using the fiber length distribution curve obtained as described above.

[0156] [Arithmetic mean curvature of the peak (Spc), arithmetic mean height (Sa), interface development area ratio (Sdr)]

[0157] The arithmetic mean curvature (Spc), the arithmetic mean height (Sa) of the peak apex of the thermally conductive sheet after polishing, and the developed area ratio (Sdr) of the interface were measured as follows.

[0158] The surface properties were analyzed using a laser microscope (VK-X150 manufactured by Keyence Co., Ltd.) in accordance with ISO 25178. Specifically, the surface profile of a two-dimensional region with a surface area of ​​1000 μm × 1000 μm was measured by a laser method under the condition of a lens magnification of 10 times. The average value of three locations measured for the same sample was used as the arithmetic mean curvature Spc of the peak vertex.

[0159] The arithmetic mean height (Sa) and the interface development area ratio (Sdr) were similarly measured at three locations on the same sample, and their average values ​​were respectively used as the arithmetic mean height (Sa) and the interface development area ratio (Sdr).

[0160] [Thermal resistance]

[0161] Thermal resistance is the value used Figure 4 The thermal resistance was measured using the method shown below using a thermal resistance measuring machine as shown.

[0162] Specifically, for each sample, a test piece S with a size of 30mm×30mm×0.2mmt was made for this test. Then, each test piece S was attached to a copper block 22 with a measuring surface of 25.4mm×25.4mm and a side covered with an insulating material 21, clamped with an upper copper block 23, and a load was applied using a load sensor 26, and the thickness was set in a manner that was 80% of the original thickness. Here, the lower copper block 22 was connected to the heater 24. In addition, the upper copper block 23 was covered with an insulating material 21 and connected to a radiator 25 with a fan. Next, the heater 24 was heated with a heat output of 25W, and 10 minutes after the temperature became roughly stable, the temperature (θ j0 ), the temperature of the copper block 22 below (θ j1 ), and the heat generation (Q) of the heater, the thermal resistance value of each sample was calculated by the following formula (1).

[0163] Thermal resistance = (θ j1 -θ j0 ) / Q…Formula (1)

[0164] In formula (1), θ j1 is the temperature of the copper block 22 below, θ j0 is the temperature of the upper copper block 23, and Q is the calorific value.

[0165] The thermal resistance value of the thermally conductive sheet before polishing and the thermally conductive sheet after polishing were measured as samples, respectively, to obtain the thermal resistance value R1 before polishing and the thermal resistance value R2 after polishing.

[0166] The thermal resistance value R2 after polishing was evaluated according to the following criteria:

[0167] (Evaluation criteria for thermal resistance R2)

[0168] A R2 is 0.022℃·in 2 / W or less

[0169] B R2 greater than 0.022℃·in 2 / W and 0.024℃·in 2 / W or less

[0170] C R2 greater than 0.024℃·in 2 / W and 0.026℃·in 2 / W or less

[0171] D R2 greater than 0.026℃·in 2 / W

[0172] The thermal resistance improvement rate (%) was calculated from the following formula and evaluated according to the following criteria: It should be noted that a higher thermal resistance improvement rate means a higher thermal resistance reduction effect achieved by polishing.

[0173] Thermal resistance improvement rate (%) = 100 × (R1-R2) / R1

[0174] (Evaluation criteria for thermal resistance improvement rate (%))

[0175] AThermal resistance improvement rate is more than 45%

[0176] BThe thermal resistance improvement rate is 40% or more and less than 45%

[0177] C thermal resistance improvement rate is 30% or more and less than 40%

[0178] D Thermal resistance improvement rate is less than 30%

[0179] [Area occupied by the piece S]

[0180] The surface of the 1 mm × 1 mm area of ​​the thermally conductive sheet was observed by surface property analysis using a laser microscope (manufactured by Keyence Co., Ltd., VK-X150), and the obtained height map (MAP) was analyzed using image analysis software WinROOF2015 (manufactured by Mitani Shoji Co., Ltd.), thereby measuring the ratio of the area at each position in the thickness direction. Then, based on the measurement results, the depth in the thickness direction from the highest point of the sheet to the deepest part of the sheet was set as 100%, and the area occupied by the sheet was calculated in the cross section perpendicular to the thickness direction at a position 40% from the highest point of the sheet in the thickness direction. The surface of the 1 mm × 1 mm area was measured at 10 locations, and the area occupied by the sheet was calculated for each measurement location, and their average value was calculated as the area S occupied by the sheet. The thermally conductive sheet before grinding and the thermally conductive sheet after grinding were used as samples, and the area S occupied by the sheet was calculated for each sample.

[0181] [Orientation ratio]

[0182] The cross section of the thermally conductive sheet was observed using an electron microscope, and 100 carbon fibers were selected to determine the number of carbon fibers oriented in the thickness direction of the sheet. The case where 61 or more carbon fibers (61%) were oriented was recorded as A, and the case where less than 60 (60%) were oriented was recorded as B.

[0183] In addition, when the direction of the major axis of the carbon fibers was within 20° with the thickness direction of the thermally conductive sheet, it was determined that the carbon fibers were oriented.

[0184] The following components were used to produce the thermally conductive sheet.

[0185] (Matrix)

[0186] Addition reaction type organopolysiloxane containing alkenyl-containing organopolysiloxane as main agent and hydrogen organopolysiloxane as curing agent

[0187] (Carbon Fiber X)

[0188] The following carbon fibers were used.

[0189] Carbon fiber 1 ... graphitized carbon fiber having an average fiber length of 110 μm, an aspect ratio of 11, and a thermal conductivity of 1200 W / m·K

[0190] Carbon fiber 2…Graphitized carbon fiber with an average fiber length of 150 μm, an aspect ratio of 15, and a thermal conductivity of 900 W / m·K

[0191] Carbon fiber 3 ... graphitized carbon fiber having an average fiber length of 200 μm, an aspect ratio of 20, and a thermal conductivity of 1200 W / m·K

[0192] Flake graphite powder··Flake, average particle size 130μm, aspect ratio 10, thermal conductivity 550W / m·K

[0193] Alumina powder··Spherical, average particle size 3μm, aspect ratio 1.0

[0194] Aluminum powder··Amorphous, average particle size 3μm

[0195] Coupling agent··n-decyltrimethoxysilane

[0196] [Example 1]

[0197] An alkenyl-containing organopolysiloxane as a matrix (polymer composition) is mixed with hydrogen organopolysiloxane (a total of 100 parts by mass), 1140 parts by mass of carbon fibers, 210 parts by mass of carbon fibers, 20 parts by mass of flaky graphite powder, 200 parts by mass of alumina powder, 100 parts by mass of aluminum powder, and 22 parts by mass of a coupling agent to obtain a mixed composition.

[0198] Next, the mixed composition is injected into a mold whose thickness is set to be sufficiently greater than that of the thermally conductive sheet, and an 8T magnetic field is applied in the thickness direction to orient the carbon fibers in the thickness direction. The mixture is then heated at 80°C for 60 minutes to solidify the matrix, thereby obtaining a block-shaped oriented molded body.

[0199] Next, the bulk oriented molded body was sliced ​​into sheets having a thickness of 250 μm using a shear blade, thereby obtaining a thermally conductive sheet (before grinding) in which carbon fibers were exposed.

[0200] Next, both surfaces of the sheet-like molded body were polished 50 times back and forth using a coarse-mesh grinding paper A (grit size #320) with an average abrasive particle size (D50) of 60 μm to obtain a polished thermally conductive sheet having a thickness of 200 μm.

[0201] [Examples 2 to 6, Comparative Examples 1 to 4]

[0202] Except having changed the composition of the mixed composition as shown in Table 1, it carried out similarly to Example 1, and produced the thermally conductive sheet.

[0203] [Table 1]

[0204]

[0205] In the thermally conductive sheets of Examples 1 to 6, the ratio of carbon fibers (A) having a fiber length of 100 μm or less and the ratio of carbon fibers (B) having a fiber length of 200 μm or more in the carbon fibers X contained in the sheets are within the ranges specified in the present invention, and the thermal resistance value is easily reduced by polishing, and the thermal resistance value after polishing is low, and the heat dissipation is excellent. This is considered to be because, in each example, the area S occupied by the sheet in a certain depth portion of the sheet after polishing becomes a large value, and thus the surface texture near the outermost surface of the sheet becomes relatively smooth.

[0206] In contrast, in the thermally conductive sheet of Comparative Example 1 in which the proportion of carbon fibers (B) having a fiber length of 200 μm or more is less than the amount specified in the present invention, and in the thermally conductive sheet of Comparative Example 2 in which the proportion of carbon fibers (A) having a fiber length of 100 μm or less is less than the amount specified in the present invention, the effect of reducing the thermal resistance value achieved by grinding is small, and therefore the thermal resistance value after grinding becomes higher than that of the sheet of the embodiment.

[0207] In the thermally conductive sheets of Comparative Examples 3 and 4 in which the proportion of carbon fibers (B) having a fiber length of 200 μm or more is greater than the amount specified in the present invention, although the effect of reducing the thermal resistance value achieved by grinding is large, since the thermal resistance value before grinding is high, as a result, the thermal resistance value after grinding becomes higher than that of the sheets of the embodiments.

[0208] Description of Reference Numerals

[0209] 10, 20 thermal conductive sheet

[0210] 14 Matrix

[0211] XCarbon Fiber

[0212] 21Insulation materials

[0213] 22The copper block below

[0214] 23 The copper block above

[0215] 24 Heater

[0216] 25 Radiator

[0217] 26 Load Cells

[0218] S test piece

[0219] θ j0 The temperature of the copper block above

[0220] θ j1 The temperature of the copper block below

Claims

1. A thermally conductive sheet comprising a matrix and carbon fibers X, wherein the matrix is ​​formed of an organic polymer and the carbon fibers X are oriented in a thickness direction of the sheet. In the carbon fibers X, the proportion of carbon fibers (A) having a fiber length of 100 μm or less is 40% or more, and the proportion of carbon fibers (B) having a fiber length of 200 μm or more is 3 to 13%. 2 . The thermally conductive sheet according to claim 1 , wherein the proportion of carbon fibers (C) having a fiber length of 50 μm or less in the carbon fibers X is 5% or less. 3 . The thermally conductive sheet according to claim 1 , wherein an average fiber length D50 of the carbon fibers X is 50 to 150 μm. The thermally conductive sheet according to claim 1 or 2, wherein the carbon fibers X have an aspect ratio greater than 2. The thermally conductive sheet according to claim 1 or 2, wherein the carbon fibers X are composed of a short-fiber carbon fiber component having an average fiber length of 50 to 120 μm and a long-fiber carbon fiber component having an average fiber length of more than 120 μm. 6 . The thermally conductive sheet according to claim 5 , wherein the content of the short-length carbon fiber component is 20 to 490 parts by mass based on 100 parts by mass of the matrix. 7 . The thermally conductive sheet according to claim 5 , wherein the content of the long-fiber carbon fiber component is 3 to 100 parts by mass based on 100 parts by mass of the matrix. 8 . The thermally conductive sheet according to claim 1 , wherein the content of the carbon fibers X is 30 to 500 parts by mass based on 100 parts by mass of the matrix. 9 . The thermally conductive sheet according to claim 1 , further comprising flaky carbon powder. 10 . The thermally conductive sheet according to claim 9 , wherein the content of the flaky carbon powder is 1 to 50 parts by mass based on 100 parts by mass of the matrix. The thermally conductive sheet according to claim 1 or 2, comprising a non-anisotropic filler. 12 . The thermally conductive sheet according to claim 11 , wherein the non-anisotropic filler is at least one selected from the group consisting of alumina, aluminum, zinc oxide, boron nitride, and aluminum nitride. 13 . The thermally conductive sheet according to claim 11 , wherein the anisotropic filler has an average particle size of 0.1 to 50 μm. 14 . The thermally conductive sheet according to claim 11 , wherein the content of the anisotropic filler is 100 to 800 parts by mass based on 100 parts by mass of the matrix. The thermally conductive sheet according to claim 1 or 2, wherein the matrix is ​​silicone rubber. 16 . The thermally conductive sheet according to claim 1 , wherein the content of the matrix is ​​20 to 50% by volume based on the total amount of the thermally conductive sheet.

17. The thermally conductive sheet according to claim 1 or 2, wherein a portion of the carbon fibers X is exposed on the surface of the sheet, and when observing the surface of a 1 mm×1 mm area, when the depth in the thickness direction from the highest point of the sheet to the deepest part of the sheet is set to 100%, an area ratio S occupied by the sheet in a cross section perpendicular to the thickness direction at a position 40% in the thickness direction from the highest point of the sheet is 65% or more.

18. The thermally conductive sheet according to claim 1 or 2, wherein The arithmetic mean curvature Spc of the peak apex of the sheet surface is 18000 or less, and the unit of Spc is 1 / mm.

19. The thermally conductive sheet according to claim 1 or 2, wherein The arithmetic mean height Sa of the sheet surface is 20 μm or less.

20. The thermally conductive sheet according to claim 1 or 2, wherein The developed area ratio Sdr of the interface on the sheet surface is 70 or less.

21. The thermally conductive sheet according to claim 1 or 2, wherein the thermal resistance is 0.024°C·in 2 / W or less.

22. The thermally conductive sheet according to claim 1 or 2, which has a thickness of 50 to 900 μm.

Citation Information

Patent Citations

  • Thermally conductive resin molded product

    JP2018014534A

  • Electromagnetic wave absorption thermal conductive sheet, method of manufacturing the same, and semiconductor device

    JP2018056315A

  • Heat conductive sheet

    WO2020067141A1

  • Heat-conductive sheet and method for producing the same

    JP2010254766A

  • Thermally conductive compact and manufacturing method thereof

    JP2014027144A